Food practices, physical activity, and perception of the nutritional status of students during confinement due to the COVID-19 pandemic (Journal on studies and research of academic knowledge, 2022)
The general objective of the research was to describe the eating practices, physical activity, and perception of nutritional status of nutrition students at the Iberoamerican University during confinement due to the COVID-19 pandemic. For this purpose, a non-experimental study was designed of a quantitative retrospective approach, through a self-administered questionnaire of 40 questions. 38 students participated in the study, mostly female (78.9%). Male students had a higher perception of malnutrition due to excess (37.5%) compared to 33.3% in female students. Regarding eating practices, it was possible to determine an insufficient consumption of dairy portions (18.4%); vegetables and fruits (39.5% and 7.9%); cereals and derivatives such as legumes (31.6%); However, if there was an increase in the consumption of meat (71%) on a daily basis, the consumption of fried or processed foods and sugars was high (58.9% and 68.4%), more than half of the students of the female sex performed less physical activity during confinement, and most of the males performed intense to moderate activities. To conclude during the confinement of the pandemic, most of the students perceived an adequate nutritional status, with insufficient consumption of dairy products, vegetables and fruits, cereals and derivatives, and water.
Keywords: Food practices; Physical activity; Confinement